2003
DOI: 10.1086/367640
|View full text |Cite
|
Sign up to set email alerts
|

Lepton Acceleration by Relativistic Collisionless Magnetic Reconnection

Abstract: We have calculated self-consistent equilibria of a collisionless relativistic electron-positron gas in the vicinity of a magnetic $X-$point. For the considered conditions, pertinent to extra-galactic jets, we find that leptons are accelerated up to Lorentz factors $\Gamma_0 = \kappa e B_0L {\cal E}^2 /mc^2 \gg 1$, where $B_0$ is the typical magnetic field strength, ${\cal E}\equiv E_0/B_0$, with $E_0$ the reconnection electric field, $L$ is the length scale of the magnetic field, and $\kappa \approx 12$. The a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 27 publications
4
76
0
Order By: Relevance
“…Stochastic acceleration by turbulence (Dermer et al 1996;Thompson 2006) or by electrostatic acceleration in reconnection layers (Romanova & Lovelace 1992;Larrabee et al 2003) are possible heating mechanisms. This implies that the high-energy tail of the prompt GRB spectrum is generated near the scattering photosphere.…”
Section: Implications For the Mechanism Of Particle Heatingmentioning
confidence: 99%
“…Stochastic acceleration by turbulence (Dermer et al 1996;Thompson 2006) or by electrostatic acceleration in reconnection layers (Romanova & Lovelace 1992;Larrabee et al 2003) are possible heating mechanisms. This implies that the high-energy tail of the prompt GRB spectrum is generated near the scattering photosphere.…”
Section: Implications For the Mechanism Of Particle Heatingmentioning
confidence: 99%
“…The magnetic reconnection might proceed in separate X-points but in average the process remains one-dimensional because the released energy is confined to a layer around the field reversal. Acceleration of relativistic electrons close to an X-point was considered by Romanova & Lovelace (1992); Zenitani & Hoshino (2001), Larrabee et al(2002) who found a powerlaw particle distribution with the slope β ∼ 1. Reconnection in a long current sheet at a time-scale large enough that particles pass many X-points has not been considered yet.…”
Section: Particle Acceleration By Driven Reconnectionmentioning
confidence: 99%
“…On the other hand, driven reconnection of the magnetic field within the shock radically alter the particle acceleration process. It follows from both analytical and numerical studies that particles are readily accelerated in the course of the magnetic field reconnection to form the energy distribution with the power-law index β ∼ 1 (Romanova & Lovelace 1992;Zenitani & Hoshino 2001;Larrabee, Lovelace & Romanova 2002). Electrons with such a distribution emit syn-chrotron radiation with a flat spectrum therefore Romanova & Lovelace (1992) and Birk, Crusius-Wätzel & Lesch (2001) suggested that reconnection plays a crucial role in flat spectrum extragalactic radio sources.…”
Section: Introductionmentioning
confidence: 99%
“…(Recall that only electrons with γ e s m p /m e can be accelerated at a relativistic shock; here s is the shock Lorentz factor, and m p and m e are the proton and electron masses.) Thirdly, acceleration in reconnection layers can produce very-hard power-law spectra, dn/dγ ∼ γ −1 (Hoshino 2002;Larrabee et al 2003). The fact that reconnection models can produce spectra that are prohibitively hard for shock acceleration can serve as a distinctive property of electromagnetic models.…”
Section: E L E C T Ro M Ag N E T I C a L Ly D O M I Nat E D J E T Smentioning
confidence: 99%